A cautious patriotism : the American churches & the Second World War - Sittser, Gerald Lawson, 1950- (University of North Carolina Press, 1997)
World War II was a turning point in twentieth-century American history, and its effects on American society have been studied from virtually every conceivable historical angle. Until now, though, the role of religion--an important aspect of life on the home front--has essentially been overlooked. In ###A Cautious Patriotism#, Gerald Sittser addresses this omission. He examines the issues raised by World War II in light of the reactions they provoked among Catholics, Episcopalians, Lutherans, Unitarians, and members of other Christian denominations. In the process, he enriches our understanding.